Implementation and optimisation of intelligent police systems based on artificial intelligence - D. O. Zhadan; M. V. Mordvyntsev; D. V. Pashniev; O. V. Khlestkov (Bulletin of Kharkiv National University of Internal Affairs)
The rapid development of artificial intelligence provides new opportunities for law enforcement agencies. Nowadays, the developed countries of the world are increasingly using surveillance cameras to monitor public safety, detect criminals and suspicious objects. The facial identification systems on the market have tremendous potential to help law enforcement agencies. Facial recognition software helps to identify missing persons and criminals whose faces are caught on CCTV cameras. The use of artificial intelligence in such systems accelerates their operation, which, in turn, facilitates the quick search for suspects and their rapid apprehension. Modern video surveillance systems can help counter terrorist attacks by tracking and identifying people and suspicious objects. On the other hand, the issue of personal data protection and privacy when using CCTV cameras to identify people's faces is increasingly being discussed. The obvious solution to this problem is to regulate it at the legislative level, in particular, to introduce guidelines aimed at ensuring transparency and accountability of the use of facial recognition software.